“STATUS” POLIGAMI DALAM REINTERPRETASI - yanto yanto; Nur Hotimah; Kurnia Badriyah Putri (El-Furqania : Jurnal Ushuluddin dan Ilmu-Ilmu Keislaman, 2018)
Polygamy in Islam is not something new as the accusations of the Orientalists who accused the Prophet Muhammad as an apostle. Polygamy before Islam had become a tradition of Arab ignorance at that time. From history we can also learn that the earlier prophets were accustomed to having more than one adult. The coming of Islam brings something new about polygamy, regardless as a shari'ah or just as an act which is permissible under certain circumstances. The purpose of this study is to see how the description of polygamy status in reinterpretation. This research uses literature literature method. The results of this study are described that polygamy is not a recommendation or command. But he is only a ruhksah that can be done on a certain condition with very strict conditions, that is, the person who is going to be polygamy should be able and fair to the wives and children. If worried can not meet the two main requirements are highly recommended to marry a woman only. If still worried about a woman then should marry her slave.